Exploitation of marine swimming crab in Coxs Bazar, Bangladesh (Bangladesh Journal of Zoology, 2013)
abstract not availableDOI: http://dx.doi.org/10.3329/bjz.v40i2.14318 Bangladesh J. Zool. 40(2): 241-245, 2012